Seeking Windows in a World of Mirrors: Zygmunt Bauman's Difficult Art of Conversation - Davis, Mark; Álvarez-Álvarez, Elena (Anthem, 2024)
This chapter reviews the main themes emerging in the last six books published by Bauman in life. In them, Bauman keeps insisting on core social such as poverty, inequity, individualisation, lack of communication and adiaphorization among the privileged part of the population towards the deprived part. But, among those themes, he accentuates the need for authentic dialogue, understood as a practice of hermeneutics and as a moral task. As such, the practice of dialogue is essential to understand deprivation, to assume responsibility for its victims, and to negotiate deep changes in our way of living, to alleviate that suffering. Bauman points to some conditions which make a dialogue “authentic” and, to this respect, he is also consistent with his former works. First, it requires critical thinking, because we are living in a fragmented world, with an increasing volume of voices, in which it becomes an arduous task to assess the real value of each voice. Critical thinking is also necessary to question, and remove, social assumptions that can be at the base of inequity. Second, dialogue must be inclusive, which means giving voice and attention to every individual or group implied by the social decisions. And third, it demands openness of mind, which implies renouncing to impose one vision, and accepting that one can be wrong. Bauman is aware that such a dialogue is difficult to conduct in the current society, but he sees in it the only hope for humanity.
Capítulo del libro: Davis, Jacobsen, M. H. (2023). The Anthem Companion to Zygmunt Bauman. London: Anthem.
Keywords: Culture; Religion; Hermeneutics; Sociology; Dialogue; Scopus(2)